The Influence of Organizational Culture on the Job Satisfaction of Teachers and Educational Personnel: A Case Study of the Educational Office, Chiang Rai Municipality - Aupathi, Thanapon; Sommanasak, Waraduang; Imiwat, Prayoon (Parichart Journal, 2025)
This research article aimed to 1) investigate the level of organizational culture factors, 2) examine the level of job satisfaction factors among teachers and educational personnel at the Education Office, Chiang Rai Municipality, and 3) analyze the specific aspects of organizational culture that influence job satisfaction among teachers and educational personnel at the Education Office, Chiang Rai Municipality. The study’s population comprised 232 teachers and educational personnel from various schools under the Chiang Rai Municipality, selected through simple random sampling. The data collection tool used was a questionnaire that had been validated for quality and reliability. Statistical analysis methods included stepwise multiple regression analysis and correlation analysis. The results revealed that 1) the level of organizational culture factors was at the highest level, 2) the level of job satisfaction factors among teachers and educational personnel at the Education Office, Chiang Rai Municipality, was also at the highest level, and 3) the analysis of organizational culture’s influence on job satisfaction, particularly adaptive culture, clan culture, and outcome-oriented culture, showed that these three factors significantly and positively impacted job satisfaction, explaining up to 49.90% of the variance. This underscored the importance of developing organizational culture to enhance job satisfaction and efficiency among teachers and educational personnel.